The role of the state in Taiwan's development - Aberbach, Joel D., ed (New York : M.E. Sharpe, 1994)
An East Gate Book
Keywords: Industrial promotion -- Taiwan; Industry and state -- Taiwan; Taiwan -- Economic policy -- 1975.